Implementasi Augmented Reality untuk Pengenalan Bangun Ruang - Silalahi, Jekson Salomo; Sejati, RR. Hajar Puji (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Solid Geometry is a part of mathematics learning that has various forms and types. The diversity of spatial shapes has area and volume formulas so that you can know the number of sides and area of each spatial shape. By utilizing Augmented Reality technology to introduce spatial structures, it makes it interesting to study. The aim of this research is to create an AR application for solid geometry in an Android-based 3D model so that it can facilitate learning in a fun way. This AR application was created using Vuforia, Unity and a marker to be able to call up the space that has been created. From this research, it is hoped that the interim results can help the learning and teaching process on spatial building materials. Application research results that can be used for the learning stage.